Potention of nHAC/PLGA Based Syringetin as Bionano Bone Graft to Improved Osteoinductivity and Osteoconductivitas - I Kadek Wahyu Putra Dyatmika; Jonathan Hubert Prasetya; I Wayan Windi Artha (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2019)
Background: According to the data of Riskesdas in 2013, fracture incident rate in Sulawesi gets a 16% increase. The most common fracture incident happens to elderly age group and its predominant cause is traumatic incident like falls and traffic accident. Treatment now such as ORIF and External Fixation is far from cheap and has a high risk to the patient. Syringetin-based nHAC/PLGA usage can be a new bionano bone graft because it can target specific cells to increase osteoinductivity in bones. Method: This literature review is established by literature review method of collecting sources from valid scientific literature which has specific inclusion and exclusion criteria. Discussion: Syringetin-based nHAC usage has some targets like BMSC. Syringetin-based nHAC has effect in increasing the expression of BMP-2 and miRNA-21. BMP-2 and miRNA-21 are factors that take part in osteoblast proliferation and differentiation. That expression increase is marked by ALP activity and osteocalcin increase. Conclusion: Significantly, the usage of syringetin-based nHAC/PLGA can increase the proliferation and differentiation rate of BMSC to osteoblast.